2021
DOI: 10.1002/jqs.3362
|View full text |Cite
|
Sign up to set email alerts
|

~5.9 cal ka bp Towada‐Chuseri tephra from Towada volcano: a mid‐Holocene marker layer from Japan to northeast China

Abstract: Far‐travelled ash layers from explosive volcanic eruptions can provide invaluable marker horizons for dating and correlating regional to global sedimentary archives. Here, we present a new cryptotephra associated with the ~5.9 cal ka bp Towada‐Chuseri eruption (To‐Cu) in a peat sediment record from northeast China. This tephra exhibits a rhyolitic glass composition that can be distinguished from other widespread tephra layers around the region of Japan and northeast China. Our findings extend the known range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…Previous visible tephra studies have shown that their dispersals do not overlap in the East Sea region (Figure 1; Machida, 1999; Machida & Arai, 2003). Our cryptotephra results, however, demonstrate that these important markers are actually co‐registered in the marine record, thus updating the information in the East Asian Holocene tephra framework (Chen et al., 2020) like other studies (e.g., Sun, Plunkett, et al., 2021, Sun, Wang, et al., 2021; Chen et al., 2022). Importantly, these new findings have significant implications, as the mid‐latitude marine archive is now able to be integrated with records in northern high‐latitudes and the tropics simultaneously (Figure 8).…”
Section: Discussionsupporting
confidence: 82%
“…Previous visible tephra studies have shown that their dispersals do not overlap in the East Sea region (Figure 1; Machida, 1999; Machida & Arai, 2003). Our cryptotephra results, however, demonstrate that these important markers are actually co‐registered in the marine record, thus updating the information in the East Asian Holocene tephra framework (Chen et al., 2020) like other studies (e.g., Sun, Plunkett, et al., 2021, Sun, Wang, et al., 2021; Chen et al., 2022). Importantly, these new findings have significant implications, as the mid‐latitude marine archive is now able to be integrated with records in northern high‐latitudes and the tropics simultaneously (Figure 8).…”
Section: Discussionsupporting
confidence: 82%